METHOD FOR IDENTIFICATION OF NONLINEAR SYSTEMS BASED ON VOLTERR SERIES IN THE TIME DOMAIN - Pavlenko , V. D.; Cherevatyi, V. V. (Problems of Informatization and Management, 2021)
A new method is proposed for identifying nonlinear systems in the form of Volterra (RW) series using deterministic test signals, based on the extraction of partial components by differentiating the system responses by the parameter-amplitude and the use of Wavelet-transformations to increase the noise immunity of the estimates of Volterra (RW) kernels.